Analysis of Factors Causing Stunting in Toddlers: A Case Study in Nagari Rawang Gunung Malelo Surantih - Hadifa, Intan Safnil; Rahayu, Sri; Akbar, Waza Karia (Journal of English Language and Education, 2025)
This study aims to analyze the causes of stunting in toddlers in Nagari Rawang Gunung Malelo Surantih, Sutera District, Pesisir Selatan Regency. Stunting is a chronic nutritional problem that remains a serious public health challenge in Indonesia. This research employed a qualitative approach with a case study method. Data were collected over a period of two months, from June to July 2024, through observation, in-depth interviews, and document analysis. The study involved 10 informants, consisting of five parents of stunted toddlers, two village midwives, and three community leaders. The results show that stunting is caused by multiple interrelated factors: economic factors (poverty and limited purchasing power), cultural factors (inappropriate feeding practices and traditional beliefs), social factors (low education levels and early marriage), and environmental factors (poor sanitation and lack of clean water facilities). Addressing stunting requires a multi-sectoral approach, including strengthening public education, improving family economic welfare, and enhancing collaboration between the government, health workers, and the community.